Alchornea cordifolia, a promising indigenous browse species adapted to acid soils in southeastern Nigeria for integrated crop-livestock agroforestry production systems - Larbi, Asamoah; Jabbar, M.A.; Orok, E.J.; Idiong, N.B.; Cobbina, J. (Springer, 1993)
Dry matter (DM) production, crude protein, phosphorus fibre contents and goat preference for eight indigenous browse species, Alchornea cordifolia, Diallum guineense, Ficus capensis, Baphia nitida, Manniophytum fulvum, Homalium aylmeri, Glyphaea brevis and Rauwolifia vomitoria, and for two exotics, Leucaena leucocephala and Gliricidia sepium, in cultivated plots were compared on acid soil in southeastern Nigeria. Total DM production was higher for Alchornea cordifolia than for the other browse species. Glyphaea brevis and L. leucocephala were the most preferred species, while A. cordifolia, G. sepium and R. vomitoria were the least. Mean crude protein content of browse species in this study was higher, while P and neutral detergent fibre were lower than reported for other browse species in Nigeria. It is argued that the ultimate goal of a crop-livestock agroforestry system such as alley farming, could be better achieved through the complementary use of browse species.